Are East Asian Companies Benefiting from Western Board Practices? - Nowland, John (Journal of business ethics, 2008)
Since the Asian crisis, East Asian nations have strived to introduce corporate governance codes, directing companies how to best improve their corporate governance practices. However, these codes have not been universally accepted by East Asian companies. This study examines the adoption of major board-related corporate governance recommendations by large non-financial companies in seven East Asian nations and investigates whether improvements in these board governance mechanisms have been associated with increased operating performance and market value. The results indicate that family-owned companies started with worse board governance and have been least likely to improve their board governance since the crisis. Overall, bigger, faster growing, non-family-owned companies with less concentrated ownership have been more likely to improve their board governance. Splitting of the positions of Chairman and CEO, creation of audit and nomination committees and improvements in overall board governance were found to have a positive relationship with subsequent operating performance and/or market value.